If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9y + -13 = 4y + 13 Reorder the terms: -13 + -9y = 4y + 13 Reorder the terms: -13 + -9y = 13 + 4y Solving -13 + -9y = 13 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -13 + -9y + -4y = 13 + 4y + -4y Combine like terms: -9y + -4y = -13y -13 + -13y = 13 + 4y + -4y Combine like terms: 4y + -4y = 0 -13 + -13y = 13 + 0 -13 + -13y = 13 Add '13' to each side of the equation. -13 + 13 + -13y = 13 + 13 Combine like terms: -13 + 13 = 0 0 + -13y = 13 + 13 -13y = 13 + 13 Combine like terms: 13 + 13 = 26 -13y = 26 Divide each side by '-13'. y = -2 Simplifying y = -2
| 2x+72y=242 | | (4a^2b^3/5)^1/2 | | 2(x-4)=6x+8 | | 81+17m=387 | | 3x-20=12+x | | 8t+6.95=24.95 | | b(a-4)=c | | 8+b+5-3b=-3-4b | | (x+3)/4=(x+5)/6 | | 5x^2-18x-6=0 | | x*x=(8.75*8.75)+(x-1)*(x-1) | | 35n-81=234 | | 4/5x7/8 | | -12=-3 | | x/(x+11)(x-11) | | 3x=5-8 | | (Y+2)=g | | 8b+1-b=8+7b+4 | | x*x=(8.67*8.67)+(x-1)*(x-1) | | z^2+i=0 | | 2d(d-2)=-7 | | x^2-3x-108= | | 38-(2c+4)=4(c+5)c | | 3x=-5x-8 | | 9x-2(3x+1)=x+1 | | -3=-9x-3 | | .09x^2-2.007x+.00012=0 | | 4(x-2)=3(x-2) | | 1/4(x-8)+7 | | x-32=-27 | | 2x-4y=12fory | | 2r+-6r=12 |